Sucrose, But Not Glucose, Blocks IL1‐β‐Induced Inflammatory Response in Human Chondrocytes by Inducing Autophagy via AKT/mTOR Pathway. Issue 3 (12th October 2016) - Khan, Nazir M.; Ansari, Mohammad Y.; Haqqi, Tariq M.
ABSTRACT: Pathogenesis of osteoarthritis (OA) is multifactorial but interleukin‐1β (IL‐1β) is known to be an important mediator of cartilage degradation. Autophagy is an essential cellular homeostasis mechanism and has been proposed to protect against cartilage degradation and chondrocyte death under pathological conditions. We investigated the role of autophagy activated by sucrose, a natural disaccharide, in suppressing inflammatory mediator's expression and cell death under pathological conditions in human chondrocytes. Autophagy activation was investigated by Western blotting for LC3 and Beclin‐1, immunofluorescence staining for LC3 puncta, and measuring autophagic flux. Activation of mTOR, AKT, and P70S6K was evaluated by Western blotting. Chondrocyte apoptosis was evaluated by propidium iodide (PI) staining using flowcytometry, expression of Bax by Western blotting, gene expression by TaqMan assays and caspase 3/7 activity was measured using a luminescence‐based assay. We found that sucrose‐induced active autophagy in OA chondrocytes in vitro was dependent on the activation of AKT/mTOR/P70S6K signaling pathways but was independent of reactive oxygen species (ROS) production. Sucrose activated autophagy blocked IL‐1β‐induced apoptosis and mRNA expression of MMP‐13, COX‐2, and IL‐6 in human OA chondrocytes. Glucose or fructose, the two metabolites of sucrose, failed to induce autophagy indicating that autophagy was specifically mediated by sucrose. In conclusion, sucrose attenuated IL‐1β induced apoptosis and the expression of catabolic mediators by inducing autophagy, and the autophagy in part was mediated through the activation of AKT/mTOR/P70S6K signaling pathway in human OA chondrocytes. J. Cell. Biochem. 118: 629–639, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Our data demonstrate that sucrose attenuate IL‐1β induced apoptosis and the expression of catabolic mediators by inducing autophagy, and the autophagy in part was mediated through the activation of AKT/mTOR/P70S6K signaling pathway in human OA chondrocytes.